Socio-Economic Determinants of Agriculture Households in Punjab: A Principal Component Analysis - Maurya, Abhilash Singh; Yadav, Bhartendu; Supriya; Sarju Narain; Atin Kumar (Indian Journal of Extension Education, 2025)
The study highlights the socio-economic determinants of agricultural families in Punjab through the main component analysis. A sample of 200 families was surveyed in 2024-25, and ten socio-economic variables were analyzed, including land ownership, income, livestock, education, family size, expansion contact, loan, mechanization, and market access. The suitability of the PCA was confirmed by a clinical test with the Kaiser-Meyer-Olkin value of 0.732 and a significant Bartlett test. The analysis highlights the three major components with more than one Eigenvector value, which cumulatively explain 68.5% of the total variance. The PC1 highlights the relevance of agricultural resources, land, livestock, and income. PC2 emphasizes human and social capital, expansion services, family labour, and education. PC3, institutional and market access, mechanization, obtained loans, and proximity to markets. The multidimensional nature of rural livelihood in Punjab is exposed, where both traditional resources and institutional factors shape domestic results. The study underlines the need for integrated policies emphasizing resource efficiency, human capacity building, and institutional strengthening to ensure inclusive and sustainable agricultural development.